Internal Migration between US States - A Social Network Analysis - Gunther Maier; Michael Vyborny (European Regional Science Association (ERSA), 2005)
In this paper we use the novel (at least in regional science) technique of social network analysis and apply it to one of the most analyzed topics in the discipline, US internal migration. We want to see whether social network analysis can yield any new insights into this well known process. We want to compare the technique to more conventional methods of analysis in migration. The paper will give an overview of recent literature about internal migration between US states and summarize the main findings. It will then present an overview of social network analysis, define key concepts and describe the main components of the technique. This discussion will also involve a discussion of currently available software for social network analysis. Then, we will apply the technique to the official data about internal migration between US states as published by the US bureau of the census, to see whether the technique can reproduce the main results of the traditional techniques and whether it can yield any new insights.
Keywords: 330